1998
DOI: 10.1021/la970843c
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrodynamic Atomic Force Microscopy Flow Cell for the Quantitative Measurement of Interfacial Kinetics:  The Aqueous Dissolution of Salicylic Acid and Calcium Carbonate

Abstract: A novel liquid flow cell allows atomic force microscopy (AFM) images to be obtained under defined hydrodynamic flow conditions, enabling reaction fluxes calculated from proposed heterogeneous reaction mechanisms to be compared with those determined experimentally. The cell employs an inclined jet to direct a fluid flow at the sample surface to cover the area under investigation including the AFM scanning cantilever tip. The flow pattern and velocity were calculated by using the finite element fluid dynamics pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 16 publications
(15 reference statements)
2
41
0
Order By: Relevance
“…As has been shown before,4–8 the data presented here demonstrate that AFM is a suitable technique for the investigation of the kinetics of surface processes. Using this technique, it was shown that the outer layer kinetics of the dehydration of trehalose dihydrate at 27–28°C and <1.5% RH followed a different model with a different rate constant when compared with the kinetics of dehydrating the whole sample.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As has been shown before,4–8 the data presented here demonstrate that AFM is a suitable technique for the investigation of the kinetics of surface processes. Using this technique, it was shown that the outer layer kinetics of the dehydration of trehalose dihydrate at 27–28°C and <1.5% RH followed a different model with a different rate constant when compared with the kinetics of dehydrating the whole sample.…”
Section: Discussionsupporting
confidence: 81%
“…The development of atomic force microscopy (AFM) has had a major impact on the understanding of surfaces 3. AFM experiments can be carried out on unprepared samples under various environmental conditions, an advantage which has been exploited by various authors to study the kinetics of surface processes, such as dissolution,4 the formation of lipid bilayers5 and the desorption of Langmuir–Blodgett films 6. There are also pharmaceutical examples of the use of AFM to study surface kinetics, both of which examined the crystallisation of amorphous lactose 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…We did not attempt to establish hydrodynamic descriptions of these flow environments (e.g., Coles et al, 1998;Higgins et al, 2002), and have instead employed sufficiently high flow rates to measure dissolution rates that reflect surface control. This strategy is consistent with many of the published AFM experiments that address both calcite dissolution (Liang et al, 1996;Liang and Baer, 1997) and growth (e.g., Teng et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…15 However, for salicylic acid, only dissolution kinetics have been investigated using in situ AFM. [16][17][18] In water, the (110) and (110) faces were studied 16 and dissolution rates determined.…”
Section: Introductionmentioning
confidence: 99%